Peran Bawaslu Sumut Dalam Mengawasi Tahapan Verifikasi Administrasi Partai Politik Calon Peserta Pemilihan Tahun 2024 Medan Barat, Sumatera Utara - Ahmad Sopiyan; Anggriyani Dinda Yasa; Rhabliani Matondang; Neni Nurhafni; Kasron Nst (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Pemilihan Umum (PEMILU) which will later be held in 2024, require every political party to complete factual verification as a condition that must be met. In Law no. 7/2017 explains that political parties that won the election in 2014 have no obligation to win elections for the next period. Certainly this policy is discriminatory towards several political parties that are relatively new, which in the end form a civil society coalition related to the review of article 173 which discusses the necessity of verification to the Constitutional Court. The analysis process in this study is to apply qualitative methods with secondary data sourced from previous research journals. Keywords: Political parties, Verification, Elections, Integrity